Enhanced particulate matter removal from flue gas of organic solid waste through acoustic agglomeration - Liu, Guicai (2025)
Fine (< 2.5 μm) and ultrafine particles (< 0.1 μm) formed from the incomplete combustion of organic solid wastes are hazardous to human health and cause damage to ecological systems due to the association with heavy metals, dioxin, etc. As such, this work demonstrates the use of acoustic agglomeration to improve the removal of these particulate matters (PMs) in a laboratory setup that mimics the hot operating conditions. The results indicate that the presence of acoustic waves improved the removal of PMs by up to 22.4 % for biomass flue gas at 30 °C. The acoustic processing temperature and fuel type were further explored. It was found that decreased temperatures (reducing from 125 °C to 30 °C) resulted in vapor condensation of moisture and organic compounds that improved collision probability due to smaller spatial distances between particles. In addition, the droplets acted as the adhesive liquid bridge to promote agglomeration after collision. Furthermore, acoustic agglomeration was found to be more effective on PMs generated from biomass, followed by municipal solid waste and plastic waste. The findings contribute significantly to the advancement of strategies for controlling fine and ultrafine particle emissions from organic solid wastes under incomplete combustion conditions, such as those found in industrial boilers and open incineration settings.